후방유수정체 안내렌즈삽입술 후 난시공막렌즈를 이용한 내부 난시의 교정 - 양승안(Seung Ahn Yang); 이지은(Ji Eun Lee) (Daihan angwa haghoi jabji, 2024)
목적: 후방유수정체 안내렌즈(implantable collamer lens [ICL], STAAR Surgical, Nidau, Switzerland) 삽입술을 시행받은 고도근시 환자에서 발생한 내부 난시를 난시공막렌즈를 이용하여 교정한 증례를 보고하고자 한다. 증례요약: 양안 ICL 삽입술을 받은 45세 남자가 시력저하로 의뢰되었다. 좌안을 먼저 교정하기로 하였고, rigid gas permeable 콘택트렌즈를 시도하였으나 불편감 때문에 착용에 실패하였다. 이에 구면공막렌즈를 처방하였으며 각막난시는 교정되었으나 내부 난시로 인하여 시력 호전에 제한이 있었다. 이는 ICL 수술 후 진행한 각막확장증, 안내렌즈의 회전으로 인한 난시로 판단되어 전면 난시공막렌즈를 처방하였으며, 이후 3개월 동안 시력은 호전되었고 착용감도 잘 유지되었다. 결론: ICL 수술 후 각막 형태의 변화 및 렌즈 위치 변화로 인해 내부 굴절오차가 발생한 경우 난시공막렌즈를 이용하여 시력 호전 및 우수한 착용감을 얻을 수 있었으며, 이는 향후 훌륭한 대안이 될 수 있을 것으로 생각된다. Purpose: We present a case of internal astigmatism correction using a toric scleral contact lens in a patient with high myopia after implantable collamer lens (ICL) surgery. Case summary: A 45-year-old man presented with a significant decrease in visual acuity despite previous ICL surgery. Initial attempts to fit a corneal rigid gas permeable contact lens to the left eye were unsuccessful due to fitting challenges. Subsequently, the use of a spherical scleral contact lens effectively corrected corneal astigmatism but failed to address internal astigmatism, thereby limiting improvement in visual acuity. Postoperative corneal ectasia and ICL rotation were suspected to be the underlying causes of this astigmatism. The introduction of a front toric scleral lens resulted in a significant improvement in visual acuity and sustained comfort throughout the 3-month follow-up period. Conclusions: The use of toric scleral lenses can significantly improve visual acuity and provide exceptional comfort in cases where corneal morphology and lens position change after ICL surgery. This modality presents a promising alternative for future consideration KCI Citation Count: 0